Age‐dependence and individual heterogeneity in reproductive success of greater sage‐grouse. (19th April 2016) - Caudill, Danny; Guttery, Michael R.; Leone, Erin; Caudill, Gretchen; Messmer, Terry A.
Abstract : Research on iteroparous species has shown that reproductive success may increase with age until the onset of senescence. However, from the population perspective, increased reproductive success with age could be a consequence of within‐individual variation (e.g. ageing, breeding experience, foraging ability hypotheses), between‐individual variation (e.g. individual heterogeneity, frailty, selection, delayed breeding hypotheses), or a combination thereof. We evaluated within‐ and between‐individual variation in reproductive success of greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse), a galliforme of conservation concern throughout western North America. We monitored female reproductive activity from 1998–2010 and used generalized linear mixed models incorporating within‐subject centering to evaluate and separate within‐ and between‐individual effects. We detected positive effects of within‐individual variation on nest initiation and success where ageing increased the likelihood of both parameters, which appears to support the breeding experience and/or foraging ability hypotheses. However, nest initiation was also affected by between‐individual variation whereby the likelihood of initiation was higher for individuals with higher mean age (i.e. survived longer), as is predicted by the frailty and selection hypotheses. Our results indicate both within‐ and between‐individual variation affect reproductive output of sage‐grouse, but the effects of each varied by measure of reproductive output. Our results corroborate previous findings that suggest population age parameters (i.e. cross‐sectional) should be interpreted with caution due to potential entanglement of within‐ and between‐individual processes. Moreover, the relative role and strength of within‐ and between‐individual processes appeared to vary by measure of reproductive output in our results, which further emphasizes the need for longitudinal analysis of age effects, even in relatively short‐lived iteroparous animals, to adequately interpret biological processes.